Single‐Step Fabrication of Polymeric Composite Membrane via Centrifugal Colloidal Casting for Fuel Cell Applications. Issue 8 (10th July 2021) - Jo, Sunhee; Yoon, Ki Ro; Lim, Youngjoon; Kwon, Taehyun; Kang, Yun Sik; Sohn, Hyuntae; Choi, Sun Hee; Son, Hae Jung; Kwon, Sung Hyun; Lee, Seung Geol; Jang, Seung Soon; Lee, So Young; et al.
Abstract: Recent interest in polymer electrolyte membranes (PEMs) for fuel cell systems has spurred the development of infiltration technology by which to insert ionomers into mechanically robust reinforcement structures by solution casting in order to produce a cost effective and highly efficient electrolyte. However, the results of the fabrication process often continue to present challenges related to the structural complexity and self‐assembly dynamics between the hydrophobic and hydrophilic parts of the constituents which in turn, necessitates additional processing steps and increases production costs. Here, a single‐step process is reported for highly compact polymeric composite membranes (PCMs), fabricated using a centrifugal colloidal casting (C3) method. Combined structural analyses as well as coarse‐grained molecular dynamics simulations are employed to determine the micro‐/macroscopic structural characteristics of the fabricated PCMs. These findings indicate that the C3 method is capable of forming highly dense ionomer matrix–reinforcement composites consisting of microphase‐separated ionomer structures with tailored crystallinity and ionic cluster sizes. An outcome that is very unlikely with the single‐step coating steps in conventional methods. These structural attributes ensure PCMs with better proton conductivity, greater strain stability, and lower gas crossover properties compared to commercial pristine membranes, expanding their possible range of applicability to PEMs. Abstract : Centrifugal colloidal casting (C3) process is employed as a single‐stage fabrication process of polymer membranes. Centrifugal force, eliminating solvent volatilization, benefits the macro‐/microscopic structure of the membrane, a compact ionomer/polytetrafluoroethylene composite structure, an ionomer structure with denser ionic aggregation, and high crystallinity. The reinforced membrane using C3 offers excellent single cell performance and mechanical properties.